2016
DOI: 10.1016/j.engfracmech.2016.02.025
|View full text |Cite
|
Sign up to set email alerts
|

Numerical investigation of fracture spacing and sequencing effects on multiple hydraulic fracture interference and coalescence in brittle and ductile reservoir rocks

Abstract: For unconventional resources exploration and development, hydraulic fracture pattern and associated dimensions are critical in determining well stimulation efficiency and ultimate recovery. When creating arrays of hydraulic fractures along horizontal wells, stress field changes induced by hydraulic fractures themselves can lead to fracture interference and coalescence. The resulting complex fracture geometry may compromise or improve the effectiveness of the stimulation job, depending on the nature of the cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
49
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 116 publications
(53 citation statements)
references
References 37 publications
4
49
0
Order By: Relevance
“…It can be observed that fractures 1 and 3 which propagate from each horizontal well turn toward each other because the induced stress-shadow effect changes the maximum principle stress at the fracture tips (see Figure 28(c)). The phenomenon that hydraulic fractures from different horizontal wells attract each other is consistent with the observation by Wang [4], Kumar and Ghassemi [50], and Wu [51]. Compared to fracture 3, fracture 1 has a larger deviation because of the stress-shadow effect induced by both fracture 2 and 3.…”
Section: Simultaneous Multifracture Propagation From Multiplesupporting
confidence: 77%
See 1 more Smart Citation
“…It can be observed that fractures 1 and 3 which propagate from each horizontal well turn toward each other because the induced stress-shadow effect changes the maximum principle stress at the fracture tips (see Figure 28(c)). The phenomenon that hydraulic fractures from different horizontal wells attract each other is consistent with the observation by Wang [4], Kumar and Ghassemi [50], and Wu [51]. Compared to fracture 3, fracture 1 has a larger deviation because of the stress-shadow effect induced by both fracture 2 and 3.…”
Section: Simultaneous Multifracture Propagation From Multiplesupporting
confidence: 77%
“…Simultaneous multiple fracturing (simul-frac) is a key hydraulic fracturing technology that fractures two or more parallel horizontal wells simultaneously, which can significantly increase the volume and surface area of the flow path to improve the productivity and recovery efficiency [2][3][4]. A great number of attempts have been made to simultaneously fracture multiple adjacent horizontal wells to generate complex fracture networks.…”
Section: Introductionmentioning
confidence: 99%
“…Fracture propagation speed and rock heterogeneity are not the main reasons leading to unstable fracture propagation and branching, it is the dynamic flow of strain energy around the fracture tip and pile-up of elastic waves in the process zone controls the instability of fracture propagation (Bobaru and Zhang 2015). Eventually, one dominant fracture will emerge from these narrowly spaced fracture swarms (Wang 2016) and will propagate further by itself until the next moment of unstable fracture propagation occurs. This can possibly explain why fracture swarms are observed in some coring samples while not observed in others (Raterman et al 2017).…”
Section: Fig18 the Analogy Between Multi-fracturing Within A Certaimentioning
confidence: 99%
“…Combining the analytic solutions of stresses and displacements with a material balance on the injected fluid, leads to the development of extensively used pressurized fracture propagation models, such as the KGD model (Geertsma and De Klerk 1969;Khristianovich and Zheltov 1955), the PKN model (Nordgren 1972;Perkins and Kern 1961), and the radial model (Abe et al 1976). Besides using analytic methods (e.g., complex potential function method and the integral transform method) to relate load, stress and displacement, numerical methods such as discrete element methods Sesetty and Ghassemi 2015;Zhao 2014), cohesive zone methods (Bryant et al 2015;Wang et al 2016), and extended finite element methods (Dahi-Taleghani and Olson, 2011;Gordeliy and Peirce, 2013;Wang 2015;Wang 2016) can be used to solve stress and displacement fields that are coupled with material balance and lubrication equations to model fluid driven fracture propagation. Even though these numerical methods enable us to model fracture propagation with complex interactions under fully coupled physics, just as analytic models, they assume smooth crack surfaces.…”
Section: Introductionmentioning
confidence: 99%